PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PT. PERKEBUNAN NUSANTARA II KEBUN HELVETIA - Purba, Daniel Gaolan; Azhmy, Muhammad Fauzan; Tamba, Muller (Universitas Harapan Medan, 2023)
The type of research used in this research is quantitative. This research was conducted at PT. Perkebunan Nusantara II Kebun Helvetia. The location of this research is on Jl. Tj. Gusta, Kec. Sunggal, Deli Serdang Regency, North Sumatra 20374. The results of the sample calculation obtained were 114 people out of the total permanent employees in the PT. Perkebunan Nusantara II Kebun Helvetia. The results of the research conducted in this thesis can be concluded that leadership style has a positive and significant effect on employee performance, reward has a positive and significant effect on employee performance, punishment has a positive and significant effect on employee performance and motivation has a positive and significant effect on employee performance.